Exogenous application of manganese and arginine alleviates the adverse effects of salinity stress on pea (Pisum sativum L.) - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Mohammed I. Al-Daej; Kholoud Ahmed El-Naqma; Adel A. Rezk; Mohamed Mabrouk El-Afry; Wael F. Shehata; Ahmed Mahmoud Ismail; Wafaa Fawzy Eltonoby; Metwaly Mahfouz Salem Metwaly (Cogent Food & Agriculture)
Salinization of water and soil presents a substantial abiotic challenge, hindering plant growth and development, causing physiological imbalances, and threatening global food security. This study aimed to investigate the effects of salinity stress at two levels (1000 and 1500 mg/L) and the potential enhancement of salinity tolerance in peas (cv. Master B) through foliar application of manganese (10 mg/L) and arginine (300 mg/L), both individually and in combination, over two consecutive seasons. Under salinity stress, various growth and yield traits of pea plants, including plant height, leaf area, plant dry weight, number of pods per plant, weight of green pods per plant, and seed dry weight, were significantly reduced compared to unstressed plants in both seasons. Physiological parameters such as chlorophyll content, antioxidant enzyme activity, membrane stability, leaf CO2 and H2O2 content, stomatal conductance, net photosynthesis, and transpiration rate were notably impacted. Biochemical seed analysis revealed significant alterations in total carbohydrate, crude protein, vitamin C, and NPK content under salinity stress. The application of manganese and arginine, either separately or in combination, alleviated the adverse effects of salinity on various parameters across different seasons. The simultaneous application was the most effective, mitigating salinity stress and resulting in improvements in total chlorophyll content (by 41.24%), proline content (17.48%), catalase activity (16.98%), peroxidase activity (22.84%), and fruit number per plant (52.14%) under the highest salinity level (1500 mg/L). Further research, including field trials and molecular studies, is recommended to fully understand the underlying mechanisms of the combined application.